Workfare, monitoring, and efficiency wages - Christian Holzner; Volker Meier; Martin Werding (Center for Economic Studies and ifo Institute (CESifo), 2006)
The impact of a stronger work requirement for welfare recipients in a workfare program is studied in an efficiency wage model where a representative firm chooses its level of monitoring activities. A stricter workfare policy raises employment and monitoring activities. It typically increases profits and reduces the tax rate. The impact on the net wage is ambiguous. Utility levels of employed workers and welfare recipients may increase even if the net wage declines. The utility differential between these two groups of workers shrinks.
Keywords: H53; J41; J60; 330